Short Term Air Conditioning System Configuration Scheme for Subway Station in Hot Summer and Warm Winter Areas - YANG Zhuo; WU Tongling; LI Xiaofeng (Chengshi guidao jiaotong yanjiu)
［Objective］ There are significant differences between the air conditioning system loads of subway stations in short term and long term. In order to avoid serious operation energy waste, the air conditioning system configuration mainly adopts variable frequency scheme or phased configuration scheme, but systematic quantitative research are still required. Therefore, it is necessary to study the air conditioning system configuration scheme for subway station operations in the short term. ［Method］ Taking a typical subway station in a city with hot summers and warm winters as an example, a load and energy consumption model that can analyze the superposed impact of actual engineering problems is established, and the model is corrected using actual test data. Two commonly used configuration schemes for air conditioning systems in subway station short-term operation are compared, and the operating energy consumption of the two schemes and the reasons for their differences are calculated and analyzed. ［Result & Conclusion］ Under ideal working conditions, i.e. the installed capacity of the equipment meets the actual load requirements and the air conditioning system is operated in variable frequency, scheme Ⅱ (phased configuration scheme) could save 19.7% energy compared to scheme Ⅰ (variable frequency scheme) ; under the most unfavorable working conditions, i.e. the installed capacity of the equipment is 50% greater than the actual load demand and the equipment frequency is not fully variable in operation, Scheme Ⅱ could save 42.1% energy compared with Scheme Ⅰ. When adopting Scheme Ⅰ, the installed capacity of the equipment should be closer to the actual load, and reasonable self-control strategies and variable frequency equipment should be adopted to ensure that the air conditioning system can be adjusted according to the actual load. When adopting Scheme Ⅱ, the resistance of the water and wind systems should be carefully calculated in the design.